Development of Islamic Boarding School Economic Areas to Improve the Welfare of Santri - Khalimi Shubhi; Lukky Aulia Rahmawati2; Safitri Putriani; Riska Riskiani (PC Ikatan Sarjana Nahdlatul Ulama Ponorogo, 2024)
The development of Islamic boarding school economic areas is a planned effort to improve the quality of human life in the economic aspect, with empowerment as one of the main approaches. This research examines the factors that influence the development of Islamic boarding schools in the economic sector, including the role of Islamic boarding school students in the empowerment process. This research uses a descriptive qualitative approach to explain the development of Islamic boarding school economic areas with the aim of improving the welfare of students. The research results show that Islamic boarding schools, as traditional Islamic educational institutions, play an important role in empowering the community's economy. In an effort to become independent and reduce dependence on other parties, Islamic boarding schools are starting to build independently managed business entities. Islamic boarding schools are also trying to expand their education into the field of sharia economics, so that they remain relevant and able to adapt to the needs of today's society. Thus, Islamic boarding schools can play an active role in the economic development of society. This research notes several economic business patterns that are generally implemented by Islamic boarding schools, including collaboration between kyai and Islamic boarding school students in agricultural businesses, Islamic boarding school economic businesses to finance their own operations, education that equips Islamic boarding school students with economic skills, and economic businesses involving Islamic boarding school alumni. Islamic boarding schools have strategic potential in increasing self-reliance, independence and community participation in economic development. They have also played an important role in the development of the cooperative sector in society. Even though it started with simple management, Islamic boarding schools have become agents of significant economic change.